Spermine application alleviates salinity induced growth and photosynthetic inhibition in Solanum lycopersicum by modulating osmolyte and secondary metabolite accumulation and differentially regulating antioxidant metabolism - Ahanger, Mohammad Abass (Plant physiology and biochemistry : PPB, 2019)
Copyright © 2019. Published by Elsevier Masson SAS.